The Pharmacological potential of lupeol and derivatives: A corroborative analysis - Sowa, Rodoshi Mahfuz (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Pharmacy, 2022.